2017
DOI: 10.1021/acscatal.7b01326
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Biojet Fuel Production from Triglyceride: Importance of the Hydrocracking Catalyst and Separate Deoxygenation/Hydrocracking Steps

Abstract: Various parameters in the catalytic hydroconversion of triglycerides (palm oil) were carefully investigated for maximizing the production of biojet fuel. The results showed that the deoxygenation of triglyceride via hydrotreatment should be carried out in a separate reactor prior to the hydrocracking step (i.e., two-step reaction process). Otherwise, the CO generated during deoxygenation can poison the metal components in the metal/acid bifunctional catalysts (Pt/zeolites), which can cause significant imbalanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 52 publications
2
60
0
Order By: Relevance
“…dehydrogenation, dehydrocyclization, hydroisomerization, hydrocracking) Pt/ZSM-5 [89] ,Pt/ZSM-22 [90] ,Pt/HZSM-5 [91] ,Pt/USY [92] ,P t/ZSM-5, % /Beta. [93] Angewandte Chemie with larger microscale bulk metals because of more exposed active sites per molar amount of metal. [40] In the last decade, the rapid development of the above-mentioned synthesis strategies provides ag ood chance to understand the unique mechanism and effects of different sizes of nanometals in zeolites.P article sizes of nanometals in zeolites have been precisely controlled, for example,n anoscale sizes by nanoencapsulation, subnanoscale sizes by traditional impregnation and atomic-scaled sites by framework fixation.…”
Section: Size Effect For Activity Enhancing:from Nanoscale To Atomic mentioning
confidence: 99%
“…dehydrogenation, dehydrocyclization, hydroisomerization, hydrocracking) Pt/ZSM-5 [89] ,Pt/ZSM-22 [90] ,Pt/HZSM-5 [91] ,Pt/USY [92] ,P t/ZSM-5, % /Beta. [93] Angewandte Chemie with larger microscale bulk metals because of more exposed active sites per molar amount of metal. [40] In the last decade, the rapid development of the above-mentioned synthesis strategies provides ag ood chance to understand the unique mechanism and effects of different sizes of nanometals in zeolites.P article sizes of nanometals in zeolites have been precisely controlled, for example,n anoscale sizes by nanoencapsulation, subnanoscale sizes by traditional impregnation and atomic-scaled sites by framework fixation.…”
Section: Size Effect For Activity Enhancing:from Nanoscale To Atomic mentioning
confidence: 99%
“…Specifically, for the production of jet diesel, the catalysts are bifunctional and are characterized by having acid sites that allow the selective function of isomerization and cracking simultaneously. Experimental evidence [34] indicate that the conversion of the n-paraffins can be described by the following reactions network:…”
Section: The Isomerization-hydrocracking Sectionmentioning
confidence: 99%
“…The exit stream from the isomerization-cracking reactor is further flashed to eliminate the hydrogen excess and the light hydrocarbons produced during the cracking step. The isomerization-cracking kinetics and reactor arrangement were taken from the open literature [34]. From Table 3 it can be observed that the bio-jet-diesel produced contains mainly i-C 8 to i-C 16 hydrocarbons indicating that a light bio-jet diesel is produced.…”
Section: The Isomerization-cracking Sectionmentioning
confidence: 99%
“…Over-cracking would cause in the production of hydrocarbons in biogasoline range, as was reported by Kim et al when using a highly acidic catalyst, platinum on zeolite catalyst. (Kim, Kim, Lee, Lee, & Choi, 2017) After the hydrotreating and hydrocracking processes, the samples were expected to have a lower free fatty acid content compared to the PFAD after the reaction through hydrotreating mechanisms. The result of FFA left in the sample, and FFA conversion from the experiments is shown in Figure 1.…”
Section: Characterization Of Pfadmentioning
confidence: 99%